Possibilidades funcionais nos usos mesoclíticos (Vaux te Vprin) - Araújo, Cléber Lemos de (2020)
The purpose of this work is to prove the existence, through frequency, that there is a type of use, similar to the mesoclitic, present in the interactions of BP, in front of the pronoun atonic te. For this purpose, we investigate the fluctuation of the use of the tonus te pronoun within verbal locational structures of the [Vaux te Vprin] type, indicating use similar to the mesoclitic and performing different functions at the syntactic and discursive levels. A descriptive-comparative study is carried out with contemporary studies on the uses of Brazilian Portuguese (BP) and European Portuguese (EP) pronouns. It is based on the theoretical assumptions of Classical Functional Linguistics - CFL and on the principles of linguistic functionalism: prototypicality and iconicity, specifically, the subprinciples of quantity and integration (HOPPER, 2001; THOMPSON, 1998; GIVÓN, 1979; FURTADO DA CUNHA; OLIVEIRA; MARTELOTTA, 2003; VOTRE, 2012; LEMOS; MATOS, 2017). The analyzed occurrences are samples from two studies carried out: the first, carried out with speakers of BP and PE by means of questionnaires / tests, dedicated to the analysis of the uses of the pronoun te in verbal locational structures of the type [Vaux te Vprin]; the second, from data extracted from the Portuguese corpus: Web/Dialects, we evaluated the productivity of the “te mesoclítico” in the four most regular verbal voice-overs in the uses of BP: "Vou te dar", "Vou te falar", "Vou te mostrar" and "Vou te contar", besides identifying the most prototypical voice-over "Vou te contar" and revealing that there are different types of uses at the syntactic and discursive level. The results show that non-canonical mesoclisis is a characteristic use of BP, while a different use movement occurs in EP. The results also show that there are four types of uses of the “te mesoclítico”: two at the syntactic level (te mesoclítico simples e te mesoclítico oracional) and two at the discursive level (te mesoclítico discursivo final e te mesoclítico discursivo inicial). As for these uses, the "te mesoclítico simples” and the “te mesoclítico oracional " are more regular with 73.4% of occurrences, while the "te mesoclítico discursivo final” and the “te mesoclítico discursivo inicial " make up 26.7% of occurrences. In any case, the presence of the percentage of occurrences with the “te mesoclítico”, within the locution "Vou te contar", especially in discursive performance, already signals a considerable linguistic fact regarding our main goal about the existence, through the frequency of use, that there is a mesoclithic type present in the interactions of BP in front of the pronoun te.